Prandtl–Reuss dynamical elasto-perfect plasticity without safe-load conditions. (March 2020) - Kisiel, Konrad; Chełmiński, Krzysztof
Abstract: In this article we study the existence theory to the Prandtl–Reuss dynamical model of elasto-perfect plasticity with non-homogeneous mixed boundary conditions. By using only the Yosida approximation of inelastic constitutive multifunction we are able to prove the existence of solutions without assuming any kind of safe-load conditions, which are quite common in the theory of elasto-perfect plasticity.